Generational accounting: an international comparison - Willi Leibfritz (Intereconomics, 1996)
With rapidly rising government debt and ageing populations implying high contingent liabilities in public pension systems, the issue of longer-term fiscal developments is gaining importance. The question arises whether, and to what extent, future generations will be burdened by current policies. Generational accounting is a new approach to examining such issues and it is used more and more in the policy debate.
Keywords: 330; Fiscal Policies